Gait instability in valproate‐treated patients: Call to measure ammonia levels. (23rd April 2017) - Kipervasser, S.; Elger, C. E.; Korczyn, A. D.; Nass, R. D.; Quesada, C. M.; Neufeld, M. Y.
Abstract : Objective: Hyperammonemia induced by valproate (VPA) treatment may lead to several neurological and systemic symptoms as well as to seizure exacerbation. Gait instability and recurrent falls are rarely mentioned as symptoms, especially not as predominant ones. Methods: We report five adult patients with frontal lobe epilepsy (FLE) who were treated with VPA and in whom a primary adverse effect was unstable gait and falls. Results: There were four males and one female patients with FLE, 25‐42‐year‐old, three following epilepsy surgery. All of them were treated with antiepileptic drug polytherapy. Gait instability with falls was one of the principal sequelae of the treatment. Patients also exhibited mild encephalopathy (all patients) and flapping tremor (three patients) that developed following the addition of VPA (three patients) and with chronic VPA treatment (two patients). VPA levels were within the reference range. Serum ammonia levels were significantly elevated (291‐407 μmole/L, normal 20‐85) with normal or slightly elevated liver enzymes. VPA dose reduction or discontinuation led to the return of ammonia levels to normal and resolution of the clinical symptoms, including seizures, which disappeared in two patients and either decreased in frequency or became shorter in duration in the other three. Conclusions: Gait instability due to hyperammonemia and VPA treatment is probably under‐recognized in many patients. It can develop when the VPA levels are within the reference range and with normal or slightly elevated liver enzymes.